Citizen’s interactions in “Smart game-playing environments” - Costa, Liliana Vale (2021)
In an increasingly networked society that opens up a set of services and opportunities to meet the citizens’ needs, one of the greatest challenges is its complexity towards the global connectivity between individuals and their surroundings. Indeed, the citizen-environment interaction is crucial for designing a ‘smart ecosystem’ in which the citizens’ context and mediated interactions are represented. So far, however, there has been little discussion about the players’ spatial mental models and kinesics cues that can foster their interactions. This position paper addresses the use of kinesics behaviours, and space semiotics in game-mediated interactions, aiming at fostering reciprocal affordances between player-citizens and their surrounding environment, for an augmented smarter game-play experience.